A Practical Guide for Aquaponics as an Alternative Enterprise - Richard Tyson; Eric Simonne (EDIS)
Aquaponics is an intensive sustainable agricultural production system that connects hydroponic and aquaculture systems to produce multiple cash crops with reduced water and fertilizer inputs. It is highly suited for small farm producers targeting local markets and agritourism opportunities. This 10-page fact sheet was written by Richard Tyson and Eric Simonne, and published by the UF Department of Horticultural Sciences, September 2014.